Developments in Management Zakat and Wakaf in Indonesia - Sinaga, Risni; Aziz, Fathul Aminudin (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
The purpose of this article is to present an overview of the development of zakat and waqf that has occurred in Indonesia. This research method focuses on managing data qualitatively using the descriptive-analysis data analysis method. The results of this research are: that the development of zakat and waqf started with the arrival of Islam to Indonesia, the application of zakat and waqf began in a simple form, and not yet fully aware of the obligation to pay zakat, waqf was first introduced with the donation of land to build a mosque. The development of zakat and waqf continues until the presence of the BAZNAS and BWI institutions which can facilitate the development, management and distribution of Zakat and Waqf in Indonesia.